Rancang Bangun Burner Dengan Variasi Jumlah Lubang Secondary Airflow 11, 13, 15, 17 Dan Diameter Lubang 5 mm, 10 mm, 15 mm Pada Tungku Gasifikasi - Saputro, Angga, Wijianto, ST, M.Eng.Sc (2017)
This research aims to determine the effect of secondary air in the furnace burners gasification reactor types updraft gasifier to the temperature of combustion flames using a variation of the hole diameter of secondary airflow 5 mm, 10 mm, 15 mm for a number of holes 17 holes, 15 holes, 13 holes and 11 holes. Fuel furnace used is rice husk with a mass of 1.5 kg of fuel that has been milled with a size of 10 mesh. The wind speed at the blower used by 10 m / s. The results of this research are known variation in the diameter and the number of secondary airflow holes affect the temperature of the fire burning on the burner. The research begins with the manufacture burner with a variety of secondary airflow hole diameter of 5 mm, 10 mm, 15 mm for a number of holes 11 holes, 13 holes, 15 holes and 17 holes. Then the primary air flow velocity in the gasification furnace which flows from the blower is set at 10 m/s. After it retrieves data that includes temperature combustion flame at the burner with intervals of every 30 seconds and a boiling water by monitoring the water temperature at intervals of every 1 minute. From this research it can be deduced that the greater the secondary air flow in the burner, the greater the temperature of the combustion flame. However, if the secondary airflow in the burner is too large it will decrease the temperature of the fire burning and water boiling time is getting longer. Referring to the results of a comparison study combustion flame temperature, time of boiling water, and the calculation of thermal efficiency in obtaining best airflow variations secondary hole on hole diameter 10 mm number of holes 11 holes. The highest temperature reached 723 ° C, the gasification process lasted 51 minutes 17 seconds is able to boil water as much as 2 kg in just 8 minutes 38 seconds has a furnace thermal efficiency of 15.16%.